IMPLEMENTATION OF THE MARKETING MIX STRATEGY TO INCREASE SALES VOLUME IN THE COVID-19 PANDEMIC - Utami Budi Utami; Eny Setyariningsih (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2022)
The importance of small and medium-sized enterprises (MSMEs) is reflected in their contribution to the national economy. Although MSME contributes significantly to the national economy, it faces many problems. While these MSMEs are being strengthened, Indonesia and the world are facing an unexpected catastrophe, the emergence of the outbreak of COVID 19. This outbreak certainly poses new short-term challenges for MSME support. The biggest challenge for MSME is the decline in demand. Declining activity and economic growth at both national and global levels have affected the decline in public demand, including the products and services produced by MSME. MSME Arin Bakery is also experiencing this. During the pandemic period from 2020 to 2021, sales declined significantly. In addition to this, there is the emergence of competitors in the same place as rising raw material prices. Community service activities are conducted in the form of mentoring and counseling to support UMKM Arin Bakery. This activity can be divided into several stages. That is the observation and question stage, the situation analysis stage, and the stage of providing input or alternative solutions. The result of this activity is in the form of a 4P marketing strategy proposal (product, price, location, promotion).